ANALISIS PENGARUH ATRIBUT PRODUK, KEBUTUHAN MENCARI VARIASI, DAN WORD OF MOUTH TERHADAP PERILAKU KEPUTUSAN PERPINDAHAN MEREK LAPTOP HEWLETT-PACKARD (HP) KE ASUS - Wibisana, Yogi; Tri Astuti, Sri Rahayu (Diponegoro Journal of Management, 2016)
Brand switching is one of the interesting objects for study. Companies need to know what motivates consumers to switch to products of competitors. The purpose of this study is to test the influence of product attributes, the variety-seeking and word of mouth to brand switching behavior of the decision on the Hewlett-Packard (HP) laptop brand to the ASUS laptop brand. For independent variables in this research consists of the product attributes (X1), need to find variation (X2), and word of mouth (X3) and the dependent variable is brand switching (Y).               The sample of 100 respondents in the area around the campus of the University of Diponegoro in Tembalang taken using purposive sampling techniques. Analysis using SPSS 11.5 which include validity test, reliability test, classic assumption test, and test the goodness of fit through multiple linear regression, F test, t test, and analysis of the coefficient of determination (R ²).                            Word of mouth showed the greatest regression coefficient so that it can be concluded that these variables are the most important factors that influence brand switching on Hewlett-Packard laptop brand to ASUS laptop brand. The second most influential factor is the product attributes, and the last is the need to find variation. Determinant coefficient (adjusted R2) of 0.520 or 52.0 percent which illustrates that the model coefficient already meet the standards of the test. The third independent variable in this study could explain 52.0 percent of the variable displacement brand. While the remaining 48.0 percent is explained by other variables outside of the three variables used in this study.